Peran Perilaku Hidup Bersih dan Sehat (PHBS) dalam Mencegah Penularan Penyakit Diare pada Balita - Afni, Fauza; Astuti, Aldian; Gussman, Gussman; Assagaf, Farha; Wally, Erny (PT.Mantaya Idea Batara, 2025)
Background: Diarrheal diseases remain a major cause of morbidity and mortality among children under five, particularly in developing countries such as Indonesia. Clean and Healthy Living Behavior (CHLB) has been widely recognized as an effective strategy to prevent the transmission of diarrheal diseases in this vulnerable population.Method: This study employed a structured literature review to evaluate the role of CHLB in reducing the incidence of diarrhea among children under five. Articles were sourced from leading peerreviewed journals published between 2018 and 2024, with a focus on CHLB practices including handwashing with soap, access to clean water, proper sanitation, and health education.Result: Findings indicate that consistent implementation of CHLB interventions especially handwashing and the use of proper sanitation facilities can reduce diarrhea risk by up to 47%. The review also identified significant challenges in CHLB adoption, particularly in remote and underdeveloped areas. These challenges include limited infrastructure, low levels of public awareness, and socioeconomic barriers.Conclusion: The promotion and implementation of CHLB significantly contribute to preventing diarrheal diseases among children under five in Indonesia. Sustained support from government sectors, infrastructure investment, and public health education are essential to overcoming existing barriers. A multi-stakeholder approach is critical to reduce the disease burden, improve child health outcomes, and achieve national child survival goals